Isomer excitation in (e, e')-reaction - I. N. Vishnevsky; V. A. Zheltonozhsky; A. G. Zelinsky; V. I. Kirischuk; N. V. Strilchuk; P. N. Trifonov (Âderna Fìzika ta Energetika, 2006)
180mTa deexcitation and 176mLu, 113mIn and 115mIn excitation cross-sections have been measured for the energy of electrons up to 3 MeV at the electron linear accelerator of Institute for Nuclear Research of National Academy of Sciences of Ukraine. For the first time 180mTa deexcitation cross-section σ (180mTa) = (9 ± 2)⋅10-30 см2 and 176mLu excitation cross-section σ (176mLu) = (1,8 ± 0,3)⋅10-30 см2 have been measured at the energy of electrons of 3 MeV.